Az apostoli királyság és a protestáns kormányzó : Horthy Miklós és a katolikus főpapok - Miklós, Péter (Közép-Európai Közlemények, 2013)
The hungarian catholic church had better political potencials in the Horthy-age (1920–1944), like formerly, in the years of the Austro-Hungarian Monarchy (1867–1918). At that time the catholicism was presented in the life of the state (parlaimentary system, adminstrition etc.) as well the world of education and the units of the regural army. However, it was a great conflict between the catholic prelates and the protestant regent. Then the heads of the hungarian church (archbishop János Csernoch, after archbishop Jusztinián Serédi) supported the inthronisation of the Habsburg family. After the death of the last hungarian king, Charles IV., the majority of the bishops believed that the legal head of state, not Miklós Horthy, but Otto Habsburg, the son of King Charles. It’s important that the catholic morality was one of the founders of the era’s official (christian and national) ideology (through the political working of bishop Ottokár Prohászka and Béla Bangha, jesuit priest). By the end of the period between the two world wars were created common interests of the church and the state (an international manifestation was the Eucharistic World Congress 1938 in Budapest). In this study the author presents the evolution of connect of the catholic prelates and the protestant regent, based on contemporary reminiscences and previously unknown archival sources.